Construction of stable fluorescent laboratory control strains for several food safety relevant Enterobacteriaceae. (December 2018) - Binet, Rachel; Pettengill, Emily A.; Hoffmann, Maria; Hammack, Thomas S.; Monday, Steven R.
Abstract: Using naturally-occurring bacterial strains as positive controls in testing protocols is typically feared due to the risk of cross-contaminating samples. We have developed a collection of strains which express Green Fluorescent Protein (GFP) at high-level, permitting rapid screening of the following species on selective or non-selective plates: Escherichia coli O157:H7, Shigella sonnei, S. flexneri, Salmonella enterica subsp. Enterica serovar Gaminera, S. Mbandaka, S. Tennesse, S. Minnesota, S. Senftenberg and S. Typhimurium. These new strains fluoresce when irradiated with UV light and maintain this phenotype in absence of antibiotic selection. Recombinants were phenotypically equivalent to the parent strain, except for S. Tennessee Sal66 that appeared Lac − on Xylose Lysine Deoxycholate (XLD) agar plates and Lac + on Mac Conkey and Hektoen Enteric agar plates. Analysis of closed whole genome sequences revealed that Sal66 had lost one lactose operon; slower rates of lactose metabolism may affect lactose fermentation on XLD agar. These fluorescent enteric control strains were challenging to develop and should provide an easy and effective means of identifying cross-contamination. Highlights: One E. coli, two Shigella and six Salmonella strains were transformed with gfp . Fluorescence, stable without antibiotic selection, can be screened using UV light. Closed genomes of lactose fermenting S. Tennessee Sal66 show loss of one lac operon. Extent of lactose metabolism in Sal66 could be identified using XLD selective agar.